Peningkatan Wisata Desa Sindangjaya Cipanas Melalui Pelatihan Pelayanan Prima: Improving Tourism in Sindangjaya Village, Cipanas, Through Excellent Service Training - Hendaris Adriyanto; Dewi Melati; Agung Gita Subakti (Information Technology and Science (ITScience), 2026)
The development of community-based tourism villages requires competent human resources (HR), especially in the area of tourist services, which are key to creating visitor satisfaction and loyalty. Good service quality not only influences the destination's image but also contributes to the local community's economic and social sustainability. Sindangjaya Village, Cipanas District, Cianjur Regency, has attractive natural tourism potential and homestay-based accommodations that continue to grow as the number of tourist visits increases. However, this potential has not been fully realized due to inadequate service standards, necessitating systematic efforts to improve the local community's human resource capacity. This study aims to improve the human resource capacity of the Sindangjaya Village community through excellent service training using an Asset-Based Community Development (ABCD) approach that emphasizes the use of local assets and the community's own potential. The method used is participatory community service activities, including training, mentoring, and outreach, for members of the Tourism Awareness Group (Pokdarwis), the main actors in managing the tourism village. Data collection was carried out through participatory observation, in-depth interviews, and post-test evaluations using pre-test and post-test instruments to measure increases in participants' knowledge and understanding. The results of the activity showed a significant increase in participants' understanding of the concepts of excellent service and effective service communication techniques, the implementation of environmental cleanliness and comfort, and a growing collective awareness of the importance of service quality in supporting the competitiveness and sustainability of tourist villages. These findings confirm that strengthening human resource capacity through local assets and the ABCD approach plays a strategic role in realizing independent, professional, and sustainable tourist villages.